Performance of Variable-Power Adaptive Modulation With Space-Time Coding and Imperfect CSI in MIMO Systems - Xiangbin Yu, Xiangbin Yu; Shu-Hung Leung, Shu-Hung Leung; Wai Ho Mow, Wai Ho Mow; Wai-Ki Wong, Wai-Ki Wong (IEEE transactions on vehicular technology, 2009)
The performance analysis of multi-input-multi-output (MIMO) systems with M-ary quadrature amplitude modulation (MQAM) and a space-time block code (STBC) over flat Rayleigh fading channels for imperfect channel state information (CSI) is presented. In this paper, the optimum fading gain switching thresholds for attaining maximum spectrum efficiency (SE) subject to a target bit-error rate (BER) and an average power constraint are derived. It is shown that the Lagrange multiplier in the constrained SE optimization does exist and is unique for imperfect CSI and for single-input-single-output (SISO) systems under perfect CSI. On the other hand, the Lagrange multiplier will be unique if the existence condition for MIMO under perfect CSI is satisfied. Numerical evaluation shows that the variable-power (VP) adaptive modulation (AM) with STBC provides better SE than its constant-power (CP) counterpart.